Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada PT Industri Jamu & Farmasi Sido Muncul Tbk Periode 2020–2024 - Luthfiyah Alvian; Nabira Araminta Wardiyah; Septyani Eka Putri; Deby Rizqi Apriliyani; Herayati Herayati (Simpati, 2026)
This study aims to analyze and evaluate the financial performance of PT Industri Jamu dan Farmasi Sido Muncul Tbk during the period 2020–2024. The research method used is descriptive quantitative by utilizing secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange (IDX) and the company's official website. Financial performance is measured through four main ratio groups, namely liquidity ratios (Current Ratio, Quick Ratio, Cash Ratio), solvency ratios (Debt to Assets Ratio, Debt to Equity Ratio), profitability ratios (Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Return on Assets, Return on Equity), and activity ratios (Total Assets Turnover, Fixed Assets Turnover). The results of the analysis show that PT Industri Jamu dan Farmasi Sido Muncul Tbk has a very healthy financial performance. The liquidity aspect shows a strong ability to meet short-term obligations. The company's capital structure is considered solvable with a low level of debt dependence. In terms of profitability, the company is able to achieve optimal and efficient profit margins. Furthermore, activity ratios confirm that operational assets are being utilized productively to generate sales. Overall, the company demonstrated stable and resilient financial growth throughout the observation period.